EVALUASI MUTU SENSORIS DAN KIMIA IKAN ASAP YANG DIBUAT DARI IKAN BAUNG (Mystus nemurus) YANG DIBERI MAKAN DIET BERBEDA - Ryan Nazmi; Bustari Hasan; Desmelati ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractThis research was to evaluate quality of smoke fish prepared from fish of different chemical composition. Two group of smoke fish were respectively prepared from Mystus catfish compositing high protein-low fat (protein 16.13 %, fat 10.69 %, A) and low protein-high fat (protein 14.75 %, fat 12.42 %, B). which were obtained from harvested fish of previous feeding trial. Both groups of fish were respectively fillet and cut into butterfly like cut and smoked in smoking kiln for 4 hour. The smoke fish were evaluated for smoking yield, sensory quality and proximate composition. The result indicate that there was no difference in smoking yield and sensory quality between smoking yield prepared from fish A and B, except appearance which was higher in smoking fish prepared from fish B. protein composition was higher to smoking fish prepared from fish A, however fat and moisture were higher in smoking fish prepared from fish B.Keywords : Smoke fish, Mystus catfish (Mystus nemurus), Smoking yield, sensory quality, Proximate composition, Protein, Fat